Determinants of Antiviral Treatment Initiation in a Hepatitis C-infected Population Benefiting from Universal Health Care Coverage. (2007) - Moirand, Romain; Bilodeau, Marc; Brissette, Suzanne; Bruneau, Julie
Abstract : BACKGROUND AND AIMS: In view of increasing therapeutic efficacy, the delivery of hepatitis C virus (HCV) antiviral treatment is expected to increase. Yet practical experience reveals a low rate of treatment, particularly among intravenous drug users. The aim of the present study was to examine the prevalence of HCV treatment and identify factors associated with HCV treatment in a population of patients evaluated in an academic hepatology outpatient clinic between 2001 and 2002. PATIENTS AND METHODS: The charts of HCV-infected patients who attended the outpatient clinic of the liver division between January 2001 and December 2002 were retrospectively reviewed. Regression analyses were conducted to compare patients according to HCV treatment initiation. RESULTS: Of 378 eligible patients (past intravenous drug users 61%), 143 (38%) initiated antiviral treatment. Enrolment in a methadone maintenance program and a strong willingness to get treatment were independently associated with treatment initiation, while current intravenous drug use, alcoholic liver damage on biopsy, precarious housing arrangements and personality disorders were negatively associated with treatment initiation. Among patients who were offered treatment, 40% refused (they did not differ from the treated group for past or current substance abuse). CONCLUSIONS: Only 38% of eligible patients initiated treatment; treatment refusal was very common. The results of the present study showed that a significant barrier to therapy involved patient perceptions.